Factors Affecting Soil Total Mercury in Seasonal Pond Basins within a Northern Hardwood Forest in Minnesota, USA. Issue 4 (18th July 2019) - Boche, Mikayla J.; DeSutter, Thomas M.; Kolka, Randall K.
Abstract : Forest canopies are sites for mercury (Hg) deposition, and forests can act as Hg sources to downstream aquatic environments. This study examined soil total Hg (THg), carbon (C), and nitrogen (N) to 15 cm in 10 seasonal pond basins in a northern hardwood forest in Minnesota. Pools (mass per area) and concentrations (mass per soil mass) of THg to 15 cm were lower in uplands than in ponds, indicating downslope transport. In uplands, THg concentrations were the same at 0‐ to 2‐cm and 2‐ to 5‐cm depths and then decreased, whereas THg density (mass per volume) peaked at 2 to 5 cm, highlighting the importance of bulk density on mass. Carbon and N trends were similar to THg. Apart from pond centers, strong positive relationships between THg and C were observed. Upland slope length, graminoid cover, basin area, and tree height accounted for over half of THg variance at pond edge. Understanding the distribution, trends, and contributing factors of soil THg can further efforts toward immobilization and sequestration, thus minimizing the potential for bioaccumulation. Core Ideas: THg uniform among basins in uplands with pond centers variable by substrate. THg greatest at pond center and uniform among upland landscape positions. Positive THg relationships with C and N, except organic pond centers. Upland THg concentration peaked at 0 to 5 cm, with mass peaking at 2 to 5 cm. Fifty‐six percent of THg pool was explained by slope length, graminoid cover, basin area, and tree height.